RONC-02. MEASURING THE EFFECT OF CLINICALLY-RELEVANT RADIOTHERAPY PROTOCOLS ON THE JUVENILE MOUSE BRAIN. (4th December 2020) - Buck, Jessica; Somers, Kale; Whitehouse, Jacqueline; Howlett, Meegan; Hii, Hilary; Strowger, Brooke; Ebert, Martin; Mehnert, Andrew; Gottardo, Nick; Endersby, Raelene
Abstract: Treatment for medulloblastoma involves craniospinal irradiation which is associated with devastating late effects. Clinical trials that simply reduce radiotherapy dosage have resulted in inferior survival rates, whereas new chemo/radiotherapy combinations that improve survival have been identified using preclinical models. However, the potential late effects of novel treatments are currently understudied and the assessment of radiation-induced late effects in mice remains challenging. Here, we aimed to measure the effect of multifractionated radiotherapy on the juvenile mouse brain as a baseline measure for future studies. NOD/Rag1-/- mice received either 8Gy whole-brain radiotherapy (WBRT) using an X-RAD SmART preclinical platform, 18Gy fractionated WBRT (9x2Gy doses), single, or multiple sham treatments beginning at postnatal day (P)16. Mice were aged to adulthood (>P63), then high resolution anatomical brain scans were obtained on a Bruker 9.4T MRI to measure the effects of WBRT on whole brain and specific regional area volumes. A single 8Gy dose (n=10) markedly reduced brain volume by 8.5% compared to single-sham controls (n=11, p<0.0001), whereas fractionated 18Gy treatment (n=7) did not cause significant differences in brain volume compared to multi-sham controls (n=4, p>0.99). Current analyses are focused on measuring treatment effects on specific areas of the brain, as well as other anatomical differences using a range of MRI techniques. These results will serve as a valuable tool to measure potential treatment-associated effects caused by novel chemo/radiotherapy combinations on the developing brain. This will enable future studies to assess the potential safety of novel treatment to inform clinical decision making.